Controlling of bacterial and fungal diseases that contaminating mulberry silkworm, Bombyx mori by using some plant extracts - Saad, Mahmoud S. I. (2021)
All tested concentrations of black seed extract increased the silk ratios of the resulted cocoons as compared to the infected control. For technological parameters, all tested extracts at 3% concentration caused the highest silk filament length; meanwhile control larvae recorded the highest silk filament weight and size. Regarding the mulberry silkworm, B. mori artificially infested with conidial solution of Beauveria bassiana when treated with all concentrations of the tested plants showed an enhancement in larval weight, pupal weight, cocoon weight, cocoon shell weight, silk filament length, and filament weight and reduced the larval mortality percentage. The highest silk filament size were recorded for the control group.